G. DELEUZE: MODEL OF NON-CLASSIC ONTOLOGY - Куцепал, С. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The main peculiarities of interpretation of ontological problems in works of G. Deleuze have been analyzed. Methodology of explication of being through the category of fold has been substantiated.